Day 2 Wed, April 24, 2019 2019
DOI: 10.2118/195426-ms
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Features of Adaptation of Oil and Gas Workers in the Arctic and in the South of Russia

Abstract: The study was carried out with the financial support of the Russian Foundation for Basic Research in the framework of the research project No. 18-013-00623. Adaptation of a person to the extreme conditions of the Arctic is a complex process of the formation of the homeostasis of the organism, which is improved from generation to generation. Adaptation is a complex systemic process of establishing the mutual correspondence of a person with the environment, which is carried out due to a certain activity of an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Regarding the construction of the bridge, the choice of an adaptation strategy may be determined by favourable environmental factors (Korneeva & Simonova, 2019). At the industrial facility under consideration, group isolation is minimal, because the fly-in-fly-out camp and the facility itself are located on the territory of the settlement.…”
Section: Research Resultsmentioning
confidence: 99%
“…Regarding the construction of the bridge, the choice of an adaptation strategy may be determined by favourable environmental factors (Korneeva & Simonova, 2019). At the industrial facility under consideration, group isolation is minimal, because the fly-in-fly-out camp and the facility itself are located on the territory of the settlement.…”
Section: Research Resultsmentioning
confidence: 99%
“…Studies by many authors have found that fly-in-fly-out workers in extractive industries may experience many problems: increased psycho-emotional stress (Khasnulin & Khasnulina, 2012), problems of psychological adaptation (Korneeva & Simonova, 2019), family relationships (Cooke et al, 2018), suicide risk (Vojnovic, 2016). The researchers also focused on studying the impact of fly-in-flyout method on health: problems of mortality (Hermansson et al, 2019), nutrition (Assis et al, 2003); sleep (Niu et al, 2017;Sachdeva & Goldstein, 2020) the relations between the locus of control and morbidity (Smith et al, 2001).…”
Section: Problem Statementmentioning
confidence: 99%
“…The third cluster includes the climatic and production factors that most affect workers and are typical for diamond mining in the Far North, which is also noted in the works of Korneeva and Simonova (2019). In other words, we can say that in the representation of object of the fly-in-fly-out work for a number of employees a separate sector is occupied by the most complex factors from the point of view of production, which require large resources to overcome them.…”
mentioning
confidence: 98%